POLA KOMUNIKASI USTADZAH ZAINIYAH DALAM MEMBINA SANTRI TAHFIDZUL QUR’AN PUTRI - Aminul 'Alimin; Saifullah Saifullah (Maddah : Jurnal Komunikasi dan Konseling Islam, 2020)
The writing of this article is motivated by the condition of Ustadzah Zainiyah successfully guiding the students to become hufadz. Though these students must actively participate in education both diniyah and general. Diniyah and general education here differ in which institutions. So that students in addition to having the obligation to deposit memorization and maintain memorization that has been deposited, he must do the tasks of educational institutions both diniyah and general. This young teacher educates his students full of patience and modesty. The conclusion that the writer got from this research is Ustadzah Zainiyah in fostering hafidzah interacting with students using interpersonal communication to get to know the participants more closely. They are grouped by Ustadzah Zainiyah with the aim that there will be intimate communication between them so that later they will not feel awkward. Interpersonal communication also occurs between fellow students, which is marked by each participant asking for their origin, their goals and so forth